Motivation, organization and career teachers: the Italian case - Bertola, Giuseppe; Checchi, Daniele (Education Policy Analysis Archives, 2014)
This article proposes to identify the objectives of the Italian educational system and its resources in order to optimize the work of teachers, and to find for each one, the most proper place, to find the proposals that may help to improve the Italian school. We also try to clear on the basis of which elections, rules and controls the Italian educational system regulates itself. In that purpose, interactions between teachers and pupils will be analyzed, to determine how the personnel selection should be carried out, how specific jobs should be assigned and in what way controls and hierarchical relations should be implemented.